Wildfire Smoke Effects on Lake-Habitat Specific Metabolism: Toward a Conceptual Understanding - Scordo, Facundo (2022)
The impacts of wildfire smoke on lake habitats remains unclear. We determined the metabolic response to smoke in the epi-pelagic and two littoral habitats in Castle Lake, California. We compared light regime, gross primary production, ecosystem respiration, and net ecosystem production in years with and without smoke. During the smoke period incident ultraviolet-B (UV-B) radiation and photosynthetically active radiation (PAR) decreased by 53% and 28%, respectively, while the water column extinction coefficient of UV-B and PAR increased by 20% and 18% respectively. Epi-pelagic productivity increased during smoke cover because of decreased solar inputs. PAR values remained sufficient to saturate productivity, suggesting observed differences were primarily the result of changes in UV-B. Littoral-benthic productivity did not change, possibly reflecting adaptation to high-intensity UV-B light in these habitats. Our results highlight the importance of understanding how prolonged wildfire smoke alters the amount of energy produced from specific habitats in lakes.